Peraturan Menteri Pendidikan dan Kebudayaan Nomor 1 Tahun 2021 Dalam Penerimaan Peserta Didik Baru (PPDB) - Risky Astagini Putri; Risti Pratami; Windyanisa Afifah Fauziana (Publikasi Indonesia, 2025)
The Indonesian government wants to equalise education in various regions. Starting in 2017, the Minister of Education has a policy that public schools can accept new students through the zoning pathway and ranked from the closest home to the school to the farthest according to the quota opened in that pathway. In addition to the zoning pathway, prospective applicants can take part in the selection through the achievement, affirmation, and parent/guardian transfer pathways. This research uses the theory of Policy Capacity by Xun Wu, M. Ramesh, and Michael Howlett. This research also uses a qualitative approach with a literature study method. The data collected comes from scientific journals, encyclopaedias, and other reliable sources relevant to the object discussed. The results of the research based on the data obtained show that although the selection is carried out quite strictly, there are still problems that occur during the process including data fraud or manipulation, illegal levies, lack of information to prospective new students and parents / guardians, and so on. Therefore, it is necessary to have an active role from the government and coordination with the school so that fraud and problems do not occur in the process of admitting new students in the following year